6x+29=-25

Simple and best practice solution for 6x+29=-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+29=-25 equation:


Simplifying
6x + 29 = -25

Reorder the terms:
29 + 6x = -25

Solving
29 + 6x = -25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-29' to each side of the equation.
29 + -29 + 6x = -25 + -29

Combine like terms: 29 + -29 = 0
0 + 6x = -25 + -29
6x = -25 + -29

Combine like terms: -25 + -29 = -54
6x = -54

Divide each side by '6'.
x = -9

Simplifying
x = -9

See similar equations:

| f(x)=x-(3/lnx) | | f(x)=x-3/lnx | | 18x-5x+4=28 | | 8x-(6x+5)=4x-21 | | 4x+2=(x-5) | | 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 | | 7(x+2)-8(4+3x)=47 | | 7(x-2)-8(4+3x)=47 | | 9x^2-100x+1000=0 | | 4x-t=14 | | (9-3g)-(3+12g)= | | log(x-1)-log(x+1)-log(8)=-2 | | 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 | | x+2x+2=2 |

Equations solver categories